Impact of mutational profiles on response of primary oestrogen receptor-positive breast cancers to oestrogen deprivation - Pascal Gellert (Nature Portfolio, 2016)
Aromatase inhibitors are used to treat oestrogen receptor positive breast cancers but the molecular basis for the response of patients is unclear. Here, the authors use samples from an aromatase inhibitor clinical trial and show that tumours from poor responders have more mutations than good responders and also more frequently harbour p53 mutations.